HERDING BEHAVIOR ANALYSIS: A CASE IN INDONESIAN STOCK MARKET - Alfarisi, Aditya Salman; Syafrina, Adelia Dwi; Ifadhoh, Nurul; Ningtyas, Mega Noerman (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research discusses herding behavior in the Indonesian Stock Exchange using the Kompas 100 Indes. Our study uses the Cross Section Absolute Deviation (CSAD) method to analyze herding behavior in three market conditions: index, bearish, and bullish. Our statistical test results show herding behavior in bearish market conditions (down), no herding behavior in the 2023-2024 market period, and bullish market conditions (up). This study shows that investors have a lot of information and use it well in analyzing the market before making investment decisions. This study's results can help understand investor behavior and reduce investment risk.